Pengaruh Jenis Elisitor Terhadap Pertumbuhan Dan Hasil Dua Varietas Tanaman Kacang Kedelai (Glycine max (L.) Merril) - Astin K Mohamad; Hayatiningsih Gubali; Sutrisno Hadi Purnomo (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Efforts to sustainably improve the resistance, growth and yield of soybean plants can be carried out through the use of elicitors. This study aimed to determine the effect of various types of elicitors and their interactions on two soybean varieties, as well as to identify the most elicitor type for enhancing the growth and yield of soybean plants. The experiment was conducted from May to July 2025 in Iloheluma Village, Tilongkabila Subdistrict, Bone Bolango Regency, Gorontalo Province. A Split Plot Design was employed with elicitor types as the main plots : E0 (no elicitor), E1 (Siam weed, Billygoat-weed, Stonebreaker, Indian copperleaf, and White leadtree), and E2 (Devil’s horsewhip leaf, Gliricidia leaf, Green chiretta, Guava leaf, and Senna tora). Soybean varieties Dega 1 (V1) and Grobogan (V2) were assigned as subplots. The results showed that elicitor types had a significant effect on the growth and yield of soybean plants, as indicated by plant height at 28 days after planting (DAP), number of leaves, 100-seed weight, and dry shelled yield per plot. In contrast, varietal treatments had no significant effect on soybean growth and yield. Moreover, there was no ineraction between elicitor types and soybean varieties across all observed parameters. The best elicitor 2 for supporting soybean growth and yield was Elicitor 2, consisting of Devil’s horsewhip leaf, Gliricidia leaf, Green chiretta, Guava leaf, and Senna tora.